Didactic strategies based on gamification to improve acaedemic performance in upper secondary students of the FIP Accounting Program - Sanchez Sanchez, Kleber Peniel; Betancourt Perenguez, Jeaneth Alexandra; Alvarado León, Beatriz Lourdes; Guzmán Hernández, Ramón (Revista Minerva, 2025)
The study examines the incorporation of gamification-based teaching strategies to address low academic performance and lack of motivation among second-year technical accounting students at FIP. The objective was to evaluate the impact of these active methodologies on students’ motivation, participation, and the development of cognitive and socio-emotional skills. The methodology employed a mixed, cross-sectional approach with a non-probabilistic sample of 23 students from the Unidad Educativa Fiscal “Capitán Giovanni Calles” (2024–2025), collecting data through digital questionnaires and interviews with three teachers. Results showed that over 90% of the students rated gamification positively, with noticeable improvements in participation, motivation, and academic performance. Teacher interviews confirmed this positive perception, although initial resistance was noted due to technological limitations and lack of training. The proposed intervention consisted of implementing gamified strategies in 40-minute class sessions, particularly in subjects perceived as difficult, to make learning more dynamic. In conclusion, gamification proved effective in enhancing academic and socio-emotional performance, fostering autonomy, and creating a participatory learning environment, positioning it as a methodology that can be replicated in other educational contexts.